Impact of Covid-19 on Tourism Industry in Bangladesh: A Narrative Review of the Period March 2020 to March 2021 - Islam, Md. Tariqul (The Indonesian Journal of Social Studies, 2021)
The objective of this study is to examine the impact of COVID-19 pandemic on the tourism industry of Bangladesh and to suggest some probable recovery strategies for minimizing the effect of COVID-19 in the tourism industry of Bangladesh. Secondary data is the heart of this study and the study has been conducted by following the three steps approaches of secondary research procedures which include developing research questions, identifying the database to answer the research questions and evaluating the collected secondary dataset. The study has found that the COVID-19 has several negative impacts on the tourism industry including the noticeable losses of revenue, a huge number of cuts off of jobs and closing the operation of the business both permanently and temporarily. Though it is near to impossible to get overcome this pandemic quickly but taking proper strategies can minimize the impact and recover the industry. This study provides an understanding of the present scenario of the impact of the COVID-19 pandemic with a guideline for future research to the academician and probable recovery strategies for the industry professional.